Pengaruh Tarif Pajak Efektif, Intenistas Persediaan dan Kepemilikan Mayoritas Terhadap Tax Avoidance pada Perusahaan Indeks Kompas100 Tahun 2017-2021 - Suci Wulandari; Hari Stiawan (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2023)
This study aims to determine the effect of the effective tax rate, inventory intensity and majority ownership on tax avoidance in companies listed on Kompas 100 for 2017-2021. This type of research is quantitative using secondary data obtained from the Indonesia Stock Exchange (IDX). The research was conducted at companies with a compass index of 100. The data sampling technique used purposive sampling, 14 companies were used as research samples with observations for 5 years 2017-2021. The results of the study show that partially the effective tax rate and majority ownership do not have a significant effect on tax avoidance, while inventory intensity has a significant effect on tax avoidance. Simultaneously the effective tax rate, inventory intensity and majority ownership have a significant effect on tax avoidance.